Learning the malaysian sign language on android platform / Norshahafiza Yusoff - Yusoff, Norshahafiza (2016)
Sign language is well-known among people which has been used in community of hearing-impaired (HI). Malay Sign Language (MSL) is a language that has been used by the deaf and hard-of-hearing community in Malaysia to communicate among them as well as with normal people also. The deaf and HI people go to special school to learn the sign language. In Malaysia, there are increasing amount in community of hearing-impaired every year. Because of the population of the community increase, the needs for normal people to know the sign language is important as they have friends among them. Nowadays, normal people are facing difficulty to apply the sign language in their daily life. In current age, technology could be utilized in order to overcome the problem. This project proposes an idea to develop a sign language learning application for normal people. The research methodology used in this project is ADDIE model. The phases in ADDIE model stated what have been done and what will this project proceed next time. For the evaluation phase, this project used summative evaluation to evaluate the result. This project is targeting the users at age 13 to 17 years old who are normal teenagers in Malaysia. As for the result, this project’s objective is firstly to develop a mobile application using multimedia elements in Android platform and secondly to test the effectiveness of the mobile application whether the normal teenagers can use that platform better.